Selective Review of Neuroimaging Findings in Youth at Clinical High Risk for Psychosis: On the Path to Biomarkers for Conversion - Ellis, Justin K.; Walker, Elaine F.; Goldsmith, David R. (Frontiers in Psychiatry, 2020)
First episode psychosis, and subsequent diagnosis of schizophrenia or schizoaffective disorder, predominantly occurs during late adolescence, is accompanied by a significant decline in function and represents a traumatic experience for patients and families alike. Prior to first episode psychosis, most patients experience a prodromal period, usually lasting 1-2 years, during which symptoms first appear and then progress. Approximately one third of patients considered to be prodromal will ultimately experience a first psychotic episode and receive a formal diagnosis of a primary psychotic disorder. Therefore, this prodromal period represents a critical window during which interventions may be targeted to slow or prevent conversion to psychosis. What is desperately needed is an ability to predict who among the prodromal, or clinically high risk, population will convert, before treatments can be targeted appropriately. This article aims to review progress made in neuroimaging in identifying possible predictive neural signatures for who will convert to psychosis. Our focus is on studies looking at structural, functional, inflammatory and neurotransmitter specific biomarkers in both cross sectional and longitudinal studies.